Membaik Pulih Imej Ummah (To Improvise the Image of the Ummah) - Safei, Su'aidi (Terengganu State Foundation Printing, 1999)
The secret of success of the past ummah refers to the slogan of the movement working together and caring society. Their focus is more to strengthen the Islamic ummah and to avoid divisive element that brings hostility and prolonged conflict.